Growth characteristics of Muzaffarnagari sheep under semi intensive feeding management - DASS, GOPAL; PRASAD, HARI; MANDAL, A; SINGH, M K; SINGH, N P (The Indian Journal of Animal Sciences, 2011)
Lambs attained their Inaximum growth during 0-3 nlonth age (pre-weaning period) as it was nearly 44% of total growth up to 12 month age (adult age). Therefore, this period of growth may be considered very crucial and proper management, feeding and health care of individual lamb should be ensured to improve overall productivity of the flocks. This would enhance the economic return of sheep breeders. Â